Endoscopic treatment of vesicoureteral reflux in pediatric patients - Jong Wook Kim; Mi Mi Oh (Korean Pediatric Society, 2013)
Endoscopic treatment is a minimally invasive treatment for managing patients with vesicoureteral reflux (VUR). Although several bulking agents have been used for endoscopic treatment, dextranomer/hyaluronic acid is the only bulking agent currently approved by the U.S. Food and Drug Administration for treating VUR. Endoscopic treatment of VUR has gained great popularity owing to several obvious benefits, including short operative time, short hospital stay, minimal invasiveness, high efficacy, low complication rate, and reduced cost. Initially, the success rates of endoscopic treatment have been lower than that of open antireflux surgery. However, because injection techniques have been developed, a recent study showed higher success rates of endoscopic treatment than open surgery in the treatment of patients with intermediate- and high-grade VUR. Despite the controversy surrounding its effectiveness, endoscopic treatment is considered a valuable treatment option and viable alternative to long-term antibiotic prophylaxis.